BANDWAGONING BRUNEI DARUSSALAM TERHADAP REPUBLIK RAKYAT CINA PADA TAHUN 2018 DALAM KONFLIK LAUT CINA SELATAN - Yehuda Purwantoro (Indonesian Journal of International Relations, 2020)
Abstract The South China Sea dispute involves People’s Republic of China (PRC) against Vietnam, Malaysia, Philippines, Indonesia, and Brunei Darussalam. The South China Sea Dispute was caused by claimant state and nine dashed line which made by PRC. Instead of resist, Brunei Darussalam in South China Sea Conflict took considerable different gesture other than the rest belligerent parties like Vietnam, Malaysia, Philipines, and Indonesia. Brunei did not show any resistance to PRC regarding territorial claimants and instead cooperates with Asian giants controversial move. Brunei Darussalam took a stand by bandwagoning against the PRC. Brunei’s behaviour was identified by Balance of Threat theory by Stephen Walt. As a result, there is a very unbalanced capability and power capacity measure between the combined power capacity of Brunei Darussalam, Vietnam, Malaysia, the Philippines, and Indonesia with PRC. It made worse by the Brunei’s economic crisis. Keywords: south china sea; brunei darussalam; people republic of china; bandwagoning. Abstrak Konflik Laut Cina Selatan melibatkan Republik Rakyat Cina (RRC) dengan Vietnam, Malaysia, Filipina, Indonesia, dan termasuk Brunei Darussalam. Konflik Laut Cina Selatan disebabkan oleh claimant state dan pembuatan sembilan garis putus-putus (nine dashed line) secara sepihak oleh RRC. Dalam menyikapi agresifitas RRC yang mengklaim wilayahnya di Laut Cina Selatan, Brunei Darussalam mengambil sikap yang berbeda dibanding yang dilakukan oleh Vietnam, Malaysia, Filipina, dan Indonesia. Brunei Darussalam mengambil sikap dengan tidak menentang klaim RRC dan melakukan bandwagoning terhadap RRC. Sikap bandwagoning yang dilakukan Brunei Darussalam disebabkan oleh tiga kondisi negara dan empat faktor ancaman dalam teori Balance of Threat Stephen Walt, dimana ukuran kapabilitas dan kapasitas kekuatan yang sangat tidak berimbang antara Brunei Darussalam, Vietnam, Malaysia, Filipina, dan Indonesia dengan RRC , bahkan jika kekuatan lima negara tersebut digabungkan. Kondisi tersebut ditambah dengan krisis ekonomi yang dialami Brunei Darussalam sehingga bandwagoning dianggap sebagai pilihan yang rasional. Kata Kunci: laut cina selatan; brunei darussalam; republik rakyat cina; bandwagoning.